Analysis of Drug Utilization in Patients with Psoriasis: A Real-World Retrospective Study Among the Italian Population - Perrone V; Losi S; Sabatino S; Mezzetti M; Dovizio M; Sangiorgi D; Degli Esposti L (Dove Medical Press, 2023)
Valentina Perrone,1 Serena Losi,2 Silvia Sabatino,2 Maurizio Mezzetti,3 Melania Dovizio,1 Diego Sangiorgi,1 Luca Degli Esposti1 1CliCon S.r.l., Società Benefit-Health Economics and Outcomes Research, Bologna, 40137, Italy; 2Eli Lilly Italy S.p.A, Sesto Fiorentino, Italy; 3Eli Lilly Italy S.p.A, Rome, ItalyCorrespondence: Valentina Perrone, CliCon S.r.l., Società Benefit-Health Economics and Outcomes Research, Via Murri 9, Bologna, 40137, Italy, Tel +39 544 38393, Fax +39 544 212699, Email valentina.perrone@clicon.itPurpose: An Italian real-world retrospective study was conducted in patients with psoriasis (PSO) to evaluate their characteristics, treatment patterns, and biological/targeted synthetic disease-modifying antirheumatic drug (b/tsDMARD) drug utilization.Patients and Methods: The retrospective analysis was carried out on real-world data collected from administrative databases of selected Italian health-departments; the dataset covered approximately 22% of the Italian population. PSO patients (identified by PSO hospitalization, and/or active exemption code and/or a topical anti-psoriatic medication prescription) were included. In prevalent patients identified during 2017- 2018-2019-2020, baseline characteristics and treatment patterns were investigated. Moreover, b/tsDMARD drug utilization (focusing on persistence, monthly dosage, and mean duration between prescriptions) was evaluated in bionaïve patients included during 2015 and 2018.Results: PSO was diagnosed in 241,552 (in 2017), 269,856 (in 2018), 293,905 (in 2019) and 301,639 (in 2020) patients. At the index date, almost 50% of patients had not received systemic medications, and 2% had received biological treatment. Among the b/tsDMARD-treated patients, a decrease in the use of tumour necrosis factor (TNF) inhibitors (60.0- 36.4%, from 2017 to 2020) and an increase in the use of interleukin (IL) inhibitors (36.3- 50.6%, from 2017 to 2020) were observed. In 2018, the persistence rates of TNF inhibitors and IL inhibitors in bionaïve patients ranged from 60.8- 79.7% and 83.3- 87.9%, respectively.Conclusion: This real-world study of PSO drug utilization in Italy showed that a significant number of patients were not treated with systemic medications and only 2% of patients were treated with biologics. An increase in the use of IL inhibitors and a decrease in the prescription of TNF inhibitors over years were found. Patients treated with biologics were highly persistent with treatment. These data provide insight into routine clinical practice for PSO patients in Italy, suggesting that the optimization of treatment for PSO still represents an unmet medical need.Keywords: psoriasis systemic medications, psoriasis biological drugs, TNF inhibitors, IL inhibitors, treatment optimization, real world evidence